2014
DOI: 10.1007/s00787-014-0557-4
|View full text |Cite
|
Sign up to set email alerts
|

Paternal influences on treatment outcome of behavioral parent training in children with attention-deficit/hyperactivity disorder

Abstract: This study aims to explore the influence of paternal variables on outcome of behavioral parent training (BPT) in children with attention-deficit/hyperactivity disorder (ADHD). 83 referred, school-aged children with ADHD were randomly assigned to BPT plus ongoing routine clinical care (RCC) or RCC alone. Treatment outcome was based on parent-reported ADHD symptoms and behavioral problems. Moderator variables included paternal ADHD symptoms, depressive symptoms, and parenting self-efficacy. We conducted repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…Adult ADHD psychosocial treatments emphasize overlearning until skills are automatic and no longer “rely” on EF abilities (Knouse & Safren, 2010). van den Hoffdakker et al (2010, 2014) reported parent ADHD did not predict negative child treatment outcomes following 12 2-hour sessions of BPT implemented over 20 weeks. Similarly, Thompson et al, (2009) reported pacing the intervention to the mother's preference.…”
Section: Parent Adhd and Child Behavior Therapy: Overview And Review mentioning
confidence: 84%
See 3 more Smart Citations
“…Adult ADHD psychosocial treatments emphasize overlearning until skills are automatic and no longer “rely” on EF abilities (Knouse & Safren, 2010). van den Hoffdakker et al (2010, 2014) reported parent ADHD did not predict negative child treatment outcomes following 12 2-hour sessions of BPT implemented over 20 weeks. Similarly, Thompson et al, (2009) reported pacing the intervention to the mother's preference.…”
Section: Parent Adhd and Child Behavior Therapy: Overview And Review mentioning
confidence: 84%
“…Of studies that reported parent ADHD did not predict child treatment outcome, flexible and individualized delivery was emphasized, such as allowing repetition and increasing treatment “dose” (Sibley et al, 2013; Thompson et al, 2009; van den Hoofdakker et al, 2010, 2014). Adult ADHD psychosocial treatments emphasize overlearning until skills are automatic and no longer “rely” on EF abilities (Knouse & Safren, 2010).…”
Section: Parent Adhd and Child Behavior Therapy: Overview And Review mentioning
confidence: 99%
See 2 more Smart Citations
“…'' Interestingly, in the current issue of European Child and Adolescent Psychiatry there is only one randomized controlled trial (RCT). Van den Hoofdakker et al [12] explored the influence of paternal variables on the outcome of behavioral parent training (BPT) in n = 83 children with attention-deficit/hyperactivity disorder (ADHD) by comparing a group receiving BPT plus ongoing routine clinical care (RCC) versus an RCC alone group. This is all the more noteworthy as across the medical sciences RCTs are often considered as the most important source of evidence.…”
mentioning
confidence: 99%